Ottoman inheritance inventories as a source for price history. Issue 3 (2nd July 2016) - Ceylan, Pınar
ABSTRACT: Ottoman historians have been severely limited by the availability and quality of primary sources from which historical prices can be compiled. This article stresses the potential of inheritance inventories for expanding the field of Ottoman price history and provides a detailed examination of the quality of the valuations in these sources. The results strongly suggest that inventory valuations are generally consistent and were closely related to the conventional prices of the time. Building upon these findings, it is reasonable to assume that the prices contained in Ottoman inheritance inventories can be reliably employed for historical research.